ANALISIS WAKTU TUNGGU RESEP PASIEN RAWAT JALAN DI INSTALASI FARMASI DI RUMAH SAKIT UMUM DAERAH TANJUNG KABUPATEN LOMBOK UTARA - Safira Maulinda; Muhammad Habibullah Aminy; Slamet Mardiyanto Rahayu; Lale Ajeng Khalifatun Wardani; Wahyu Aprilyaningsih (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2025)
This study aims to analyze the prescription service waiting time for outpatients at the Pharmacy Installation of Rumah Sakit Umum Daerah Tanjung, North Lombok Utara Regency. A descriptive approach was employed, with data collected through direct observation and recording of waiting times from the moment prescriptions were received until medications were dispensed to patients. The findings indicate that waiting times vary depending on the type of medication and patient visit conditions. For prescriptions containing non-compounded (ready-made) and compounded medications, the waiting time generally ranges from 30 to 60 minutes, with an optimal time of less than 15–30 minutes for non-compounded medications in the absence of constraints. Meanwhile, for compounded prescriptions, the maximum waiting time can reach 50–60 minutes and, under normal conditions, can be completed within approximately 45 minutes. Waiting times tend to increase during peak patient volumes and when obstacles arise, such as the need for confirmation with the prescribing physician. These results suggest that workload factors and prescription complexity significantly influence the speed of prescription services in the pharmacy installation, highlighting the need for service management optimization to enhance the quality and efficiency of pharmaceutical care services.